MODERN ASPECTS OF THE PRACTICAL TRAINING OF FUTURE DENTISTS - L.F. Kaskova; S.Ch. Novikova; O.V. Khmil; N.V. Yanko; N.A. Morgun; I.Yu. Vashchenko (Український стоматологічний альманах, 2022)
Abstract. An important and one of the main directions in the field of higher medical education is the necessity of significant strengthening of the practical aspect of training of future doctors and saving the appropriate level of theoretical knowledge.